Expanded Pharmacy Practice Implementation: Lessons from Remote Practice - Selina Taylor; Alice Cairns; Beverley Glass (Pharmacy, 2022)
Aim: The aim of this study is to explore pharmacist perspectives of the implementation of a community pharmacy-based ear health service in rural communities. Method: A community pharmacy-based health service model was designed and developed to provide an accessible ear care service (LISTEN UP—Locally Integrated Screening and Testing Ear aNd aUral Program) and pharmacist’s perspectives of the implementation of LISTEN UP were explored. Thematic analysis was conducted and data coded according to the Consolidated Framework for Implementation Research. Results: A total of 20 interviews were conducted with 10 pharmacists, averaging 30 min. Visualistion of the ear canal was reported as the greatest advantage of the service, whilst the time required for documentation reported as a complexity. The number of pharmacists working at one time and the availability of a private consultation room were identified as the two limiting factors for execution. On reflection, the need for government funding for service viability and sustainability was highlighted. Discussion/Conclusion: Expanded pharmacy practice is emerging for the Australian pharmacy profession. Rural community pharmacists are recognised as integral members of healthcare teams, providing accessible medication supply and health advice to seven million people in Australia who call rural and remote regions home. However, there are no structured models supporting them to provide expanded services to improve health outcomes in their communities. This study provides lessons learnt to guide future design and development of expanded models of pharmacy practice.